Disparities in Emergency Transport of Women with a Preterm Labor Diagnosis in Urban vs Rural Areas in the US - Vilalta A; Troeger KA (Dove Medical Press, 2020)
Adrian Vilalta,1 Kathleen A Troeger2 1Market Access Department, Hologic, Inc., San Diego, CA, USA; 2Market Access Department, Hologic, Inc., Marlborough, MA, USACorrespondence: Adrian Vilalta Email Adrian.Vilalta@hologic.comObjective: This study evaluated patterns of utilization and costs of emergency transport among women with a diagnosis of preterm labor in the US.Methods: The IBM® Treatment Pathways® tool was used to interrogate a cohort randomly selected from the IBM’s MarketScan® dataset. Differences in costs and utilization patterns were assessed by the type of emergency transport service and geography.Results: A cohort of 12,995 women between the ages of 16 and 45 met the inclusion criteria. About 1,029 (7.9%) of these women had evidence of emergency transport within a day of the preterm labor diagnosis. In this cohort, the median cost of emergency ground transportation was US$834; air transport had a median cost of US$22,922. Additionally, 3.1% (284) women out of a cohort of 8,728 women ages of 16 and 45 with a diagnosis of false labor required emergency transport within 7 days suggesting that they were discharged too soon.Discussion: The prevalence of emergency transport for preterm labor in rural areas is significantly higher compared to non-rural areas. In addition, the disproportionate use of air transport in rural areas increases the costs of the preterm labor event. Moreover, disparities in both utilization rates and costs were identified for different parts of the country.Keywords: preterm labor, emergency transport, cost, rural, urban, disparities